Ultrasound outcomes and surgical parameters of the double-layer purse-string uterine closure technique in cesarean delivery: a systematic review and meta-analysis of randomized trials - Mahsan Nabighadim; Maryam Vaezi; Mahsa Maghalian; Mojgan Mirghafourvand (BMC Surgery)
Abstract Background A cesarean scar defect is a structural abnormality in the myometrium at the site of a prior cesarean incision, primarily influenced by the closure technique. Purse-string uterine suturing (PSUS) may reduce the incidence of cesarean scar defects and improve uterine integrity. However, the literature presents inconsistent findings, necessitating a systematic evaluation. This systematic review and meta-analysis of randomized controlled trials (RCTs) aims to assess the impact of PSUS on ultrasound outcomes and surgical parameters related to cesarean scars. Methods This systematic review and meta-analysis involved a search for relevant publications in English and Persian across multiple databases, including PubMed, the Cochrane Library, Google Scholar, Scopus, Web of Science, and SID. The search was unrestricted by date and included all available publications up to August 8, 2024. The risk of bias in the included studies was evaluated using the Risk of Bias 2 (ROB2) tool, while the certainty of the evidence was assessed through the GRADE approach. Meta-regression was employed to investigate potential risk factors for cesarean scar defects, and trial sequential analysis was conducted to mitigate Type I and Type II errors. Results A total of 353 studies were identified through the search strategy, with 8 studies included in the analysis. The meta-analysis demonstrated a significant reduction in the rate of cesarean scar defects in the PSUS group compared to the control group (risk ratio [RR] 0.45, 95% confidence interval [CI] 0.36 to 0.58; 8 trials, 751 participants, I² = 0%, indicating no heterogeneity). Additionally, a shorter uterine incision length was observed in the PSUS group compared to the control group (MD -3.84, 95% CI -4.97 to -2.71; 4 trials, 438 participants, I² = 80%, suggesting substantial heterogeneity). The PSUS group also exhibited greater residual myometrium thickness (RMT) than the control group (MD 1.33, 95% CI 0.72 to 1.94; 5 trials, 417 participants, I² = 92%, indicating considerable heterogeneity). However, no statistically significant differences were found between the PSUS and control groups regarding operation time (p = 0.10, I² = 67%, suggesting moderate heterogeneity), length (p = 0.14, I² = 98%, indicating considerable heterogeneity), height (p = 0.10, I² = 76%, suggesting substantial heterogeneity) of incision defects, or blood loss during the procedure (p = 0.94, I² = 0%, indicating no heterogeneity). Conclusions The use of PSUS during cesarean sections significantly reduces the occurrence of cesarean scar defects, indicating a clear clinical benefit with moderate certainty. However, the evidence for other ultrasound evaluation outcomes and surgical parameters remains of low to very low certainty. Therefore, further research is essential to validate these findings and assess the long-term clinical implications of integrating PSUS into cesarean procedures.